The significance of the digitalization and online communication tools used by five-star restaurants in Bulgaria - Mariya Stankova; Svetoslav Kaleychev (Tourism)
The changes undergone by the tourism industry in the past four years have dramatically affected its way of doing business and communicating with customers. A trend in this process is the penetration of digital technologies and their use as a communication channel and tool of influence. A new way of interacting with tourists has arisen, accompanied by adaptive and innovative business strategies. Bearing in mind these structural and functional changes, the present study aims to analyse one of their aspects, namely the significance of the usage of various online communication tools in the restaurant sector in Bulgaria. The assumption that the interactivity of restaurant websites helps to increase interest and attract visitors, thereby stimulating development, is investigated.